Graphene-encapsulated Si on ultrathin-graphite foam as anode for high capacity lithium-ion batteries - Ji, Junyi (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.